Issues and Challenges of Teaching English for Professional Communication. - Bortnyk, Svitlana (Universitatea de Stat „Bogdan Petriceicu Hasdeu” din Cahul, 2025)
In many professional environments, English proficiency is essential for career growth. Teaching appropriate, industry-specific language, ESP classes give learners practical skills needed for professional communication within their respective areas of activity. ESP courses emphasize the functional use of English in real-world settings. The integration of the three strategies—needs analysis, authentic materials, and blended learning approaches will bring to significant improvements in learners’ results. Learning a foreign language for special purposes provides a student with an excellent opportunity to acquire good foreign language reading skills. Considering all the challenges of today, teachers of foreign languages for special purposes should undergo special training in certain skills, especially such as needs analysis and materials preparation.
Engleză pentru scopuri specifice/speciale, comunicare profesională, terminologie, predarea lecturii, analiza nevoilor
Keywords: English for Specific /Special Purposes, professional communication, terminology, teaching reading, needs analysis